Vertical Fine-Scale Distribution of Calanus sinicus in the Yellow Sea Cold Water Mass During the Over-Summering Process - Pan, Jun; Cheng, Fangping; Yu, Fei; Shi, Yongqiang; Sun, Fan; Si, Guangcheng; Wei, Chuanjie; Diao, Xinyuan; Zhao, Yongfang (Frontiers in Marine Science, 2021)
Calanus sinicus, a temperate copepod with > 27 °C lethal temperature, is one of the key species of Chinese coastal marine ecosystem. Calanus sinicus population regularly prospers in spring and declines in early summer annually due to increasing water temperature. Then, numerous C. sinicus individuals congregate in the Yellow Sea Cold Water Mass (YSCWM) and remain under the thermocline from early summer to early autumn. They stop development and reproduction in this cold and foodless bottom water and avoid ascending to the hot surface water, which is regarded as over-summering strategy. Based on discrete water sampling approaches, previous studies demonstrated that the higher values of chlorophyll a appeared in the mixed hot surface water layer, however, the subsurface chlorophyll a maximum layer (SCML) was seldom described. In the present study, various probes and Visual Plankton Recorder (VPR) were used to explore the fine vertical distributions of environmental factors and C. sinicus. VPR observations showed the ecological responds in fine scale and indicated that few C. sinicus individuals ascend at night, the main population preferred to stay below the SCML all day long. The results highlighted that existed constant thin SCML in the YSCWM area, and the SCML was located coincided with or beneath the thermocline and halocline layers, where the temperature was suitable for C. sinicus. The relationship between abundance and Chla, show the diel vertical migration trend of C. sinicus to feed at night from the YSCWM station. In addition to temperature as the main influencing factor, DO concentrations and the column depth are also influential factors. Therefore, in addition to avoiding high surface temperature, energy supplement might be an important driving force confining diel vertical migration of C. sinicus in the Yellow Sea in summer.